STEAM APPROACH AND HIGH SCHOOL EDUCATION: A NEW LANGUAGE FOR YOUTH EDUCATION? - Maciano, Giseli Duardo (2024)
When asking about a new language for youth education, in the digital age, we are compelled to think about pedagogical practices designed to serve this audience that navigates cyberspace. In this sense, this study proposes to present the STEAM approach (acronym for Science, Technology, Engineering, Art and Mathematics) by different authors and contexts, considering the current reform of secondary education, focusing on the state of Mato Grosso. The objective is to analyze the evolution of the STEAM approach and its articulation with such reform, based on the problem: What contribution can the STEAM approach promote in the teaching and learning process of students in basic education, especially in high school? This question motivated exploratory research with a bibliographic and documentary design, which, based on the Protagonism and Life Project categories, operationalized the content analysis in the Mato Grosso Curricular Reference Document - High School stage (DRC/MT-EM). The contribution of this research is in the dialogue between STEAM and the new structure for High School, showing possible paths in this trajectory, highlighting the development of policies that contemplate a new language for youth education, in order to enable new perspectives on resignification of pedagogical practices within the school space.